The Implementation of Program “Desa Mandiri Benih" (Self-Sufficient Seed Villages) for Promoting Farmers Welfare (Study in Mempawah Regency, West Kalimantan, Indonesia) - Sriwidyanty, Endang; Hermawan, Hermawan; Amin, Fadillah (Jurnal Ilmiah Administrasi Publik, 2018)
This study discussed the implementation of Self-sufficient seeds village program in Mempawah Regency, West Kalimantan as an effort of the Government to develops seeds independency in villages and able to provide quality seeds. The study conducted using descriptive qualitative approach using the program implementation theory by David C. Korten (1980). Respondents were composed of participant and non-participants farmers of the Self-sufficient seed villages program. The results showed that in terms of three elements of program content and context of Implementation on supports the program implementation were running well.It is important to observe the sustainability of this program at the end of it farmers would then be able to produce high quality seeds continuously with or without government programs.